Sayyidunā Ibrāhīm ibn Muḥammad ﷺ: Historical Narratives and Eternal Lessons from His Brief Life - Dr. Amir Hayat; Lubna Iftikhar (Al Manhal Research Journal, 2025)
Sayyidunā Ibrāhīm ibn Muḥammad ﷺ, the son of Muḥammad ﷺ and Māriya al-Qibṭiyya (RA), is briefly described in the event in his lifetime in this article. In His short life there are a lot of spiritual lessons for the Muslims, yet Ibrāhīm ibn Muḥammad ﷺ lived only sixteen months, but his life highlighted the major events of the Holy Prophetﷺ 's life. This article explores the historical events, including his birth, which was a sign of joy for the Holy Prophet ﷺ and all Ummah at that time; the Holy Prophet's ﷺ delegation to the wet nurse; the Holy Prophetﷺ's love as a father; the status of His mother which is changed from slavery to "Umm al-Walad.", Holy Prophet ﷺ emotional response to his death; and the clearness of the superstition which spread after his death. Along with descriptive research, the study highlights the moral and ethical lessons that may be learnt from these incidents, including the importance of love for children, the way Islam views grief and how to manage it, and the rejection of superstitious beliefs. The study explains how Ibrāhīm ibn Muḥammadﷺ 's brief life provides guidance in the areas of emotional guidance, parental love, and obedience to Allah's decree by explaining the historical narratives of Islamic sources and the sociocultural background. It also helps to give a deeper understanding of the Holy Prophet's ﷺ human emotions within the framework of faith.